2018
DOI: 10.1158/1078-0432.ccr-17-1365
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Homing Therapy for Reducing Regulatory T Cells and Preserving Effector T-cell Function in Large Solid Tumors

Abstract: Infused autologous tumor-infiltrating lymphocytes (TIL) and tumor-targeted chimeric antigen receptor (CAR) T cells typically surround malignant lesions or penetrate small tumor nodules but fail to penetrate large solid tumors, significantly compromising their antitumor impact. Strategies to overcome this primary challenge are largely required. We tested the effects of plus doxorubicin on T-cell penetration and efficacy in solid tumors in a murine lung cancer model, a murine breast carcinoma lung metastasis mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 49 publications
2
34
0
3
Order By: Relevance
“…(Table 1 and full data in Supplemental Table 2 ). The estimated anti-proliferative and cell-killing effects of palbociclib and dinaciclib are consistent with published mechanisms(10, 16).…”
Section: Resultssupporting
confidence: 88%
“…(Table 1 and full data in Supplemental Table 2 ). The estimated anti-proliferative and cell-killing effects of palbociclib and dinaciclib are consistent with published mechanisms(10, 16).…”
Section: Resultssupporting
confidence: 88%
“…For instance, IL-2 is the first effective immunotherapy of human cancer but it is also known to be very toxic (Rosenberg, 2014). IL-12 exhibits potent anti-tumor activity (Colombo and Trinchieri, 2002) via promoting Th1/Tc1 response (Colombo and Trinchieri, 2002;Del Vecchio et al, 2007) and enhancing T cell trafficking to tumors through induction of chemokines (Hu et al, 2018). However, systemically delivered IL-12 causes fatal toxicity (Car et al, 1995;Ryffel, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that Tregs contribute to inhibition of the anti‐tumour immune response . The efficacy of many immunotherapeutic approaches that target T cell co‐inhibitory and co‐stimulatory receptors correlate with an altered balance in the ratio of effector T cells to Tregs in favour of the effector cells . Despite the evidence that Tregs inhibit tumour immunity, the question remains as to where and through what mechanism do Tregs inhibit the anti‐tumour immune response .…”
Section: Discussionmentioning
confidence: 99%
“…20 The efficacy of many immunotherapeutic approaches that target T cell co-inhibitory and co-stimulatory receptors correlate with an altered balance in the ratio of effector T cells to Tregs in favour of the effector cells. 21 Despite the evidence that Tregs inhibit tumour immunity, the question remains as to where and through what mechanism do Tregs inhibit the anti-tumour immune response. 8 Notably, we identified that the percentage of CD4 + CD25 + CD127 low Tregs was significantly increased and was related to lymphatic invasion in EOC.…”
Section: Discussionmentioning
confidence: 99%